Everyone's a teacher, everyone's a student - Elliot, Dominic (Technical Centre for Agricultural and Rural Cooperation, 2006)
While HIV/Aids continues to imperil the agricultural workforce across Africa, an Aids support group in Malawi is using participatory video to boost their self-esteem and to encourage others to get tested.